ERROR ANALYSIS OF SUBJECT-VERB AGREEMENT MADE BY STUDENTS IN MEURANDEH LANGSA - Reny Lestari Indah; Rasyid Gunawan; Putri Mulyani (Universitas Islam Sumatera Utara (UISU), 2018)
This research aimed at identifying the subject-verb agreement errors in students’ writing. This research applied a descriptive research. The data were collected through test and non-test instruments. Test instruments were conducted through writing test and non-test instruments were through questionnaire and interview. The data obtained from both test and non-test instruments were conducted by employing descriptive analysis. This research analyzed students’ narrative writing based on Surface Strategy Taxonomy proposed by Dulay, Burt and Krashen (1982). This result revealed the types of error in subject-verb agreement in the students’ narrative writing covering omission, addition and misinformation. In conclusion, the students involved in the research made a number of errors. It was found that the students’ ability to use subject-verb agreement in English was still low.